ChemInform Abstract: Synthesis and Applications of Silyl 2‐Methylprop‐2‐ene‐1‐sulfinates in Preparative Silylation and GC‐Derivatization Reactions of Polyols and Carbohydrates. Issue 31 (14th July 2016) - Markovic, Dean; Tchawou, Wandji Augustin; Novosjolova, Irina; Laclef, Sylvain; Stepanovs, Dmitrijs; Turks, Maris; Vogel, Pierre
Abstract: Trimethylsilyl, triethylsilyl, tert‐butyldimethylsilyl, and triisopropylsilyl 2‐methylprop‐2‐ene‐1‐sulfinates are prepared by Cu‐catalyzed sila‐ene reactions of methallylsilanes with SO2.